Management of Oil Revenues: Has That of Azerbaijan Been Prudent? - Sarvar Gurbanov; Jeffrey B. Nugent; Jeyhun Mikayilov (Economies, 2017)
To help explain the common failure of oil or other natural resource exporting countries to diversify into industry, it has been common to trace this failure to real exchange rate appreciation. This has also been done in Azerbaijan. However, because Azerbaijan has devoted so much of its oil revenues to government investment, Azerbaijan provides a suitable case for examining an alternative link through government investment. This study applies the ARDL cointegration method to quarterly time series data on oil prices, government capital formation, non-oil exports and non-oil GDP to estimate the long run relationships linking oil prices to government investment expenditures and further to generation of non-oil GDP. The results show that despite the massive government investment expenditures, extremely little non-oil production of the tradable type has been generated, calling attention to the need for policy reform.
Keywords: Q01; Q32; Q43; H54; 330; oil windfall gains; Dutch Disease